Tumorspheres Derived from HCC Cells are Enriched with Cancer Stem Cell-like Cells and Present High Chemoresistance Dependent on the Akt Pathway - Zhang, Xiao-Li; Jia, Qian; Lv, Lin; Deng, Tao; Gao, Jian (Anti-Cancer Agents in Medicinal Chemistry, 2015)
Recent evidence suggests that a small subset of cells within tumors have ‘stem cell-like’ characteristics. However, direct proof of the population of liver CSCs remains elusive. Further research is needed to identify cells with stem cell properties in established HCC cell lines. Our previous investigation found that tumor spheres are essentially enriched in CSCs. We hypothesized that chemoresistance in hepatocellular carcinoma (HCC) is due to enrichment of cancer stem cells via the PI3K/Akt pathway. We found that tumor spheres cells formed from HCC cells contained a high percentage of CD90+ cells, and these cells were more tumorigenic and resistant to doxorubicin (DOX), showing a higher proliferation rate and lower apoptosis rate compared to cells in monolayer culture. Treatment with DOX and PI3K/Akt inhibitor increased apoptosis and reduced viability among cells in the tumorspheres. The expression of p-Akt1 was upregulated in tumorsphere-forming cells treated with DOX but downregulated upon further treatment with the PI3K/Akt inhibitor. Our results demonstrate that HCC cells in tumorspheres with cancer stem cell properties achieve chemoresistance via the PI3K/Akt1 pathway.
Keywords: tumorsphere